Experience of operating a solar parabolic trough direct steam generation power plant with superheating. (1st September 2018) - Willwerth, Lisa; Feldhoff, Jan Fabian; Krüger, Dirk; Keller, Lothar; Eickhoff, Martin; Krüger, Joachim; Pandian, Yuvaraj; Tiedemann, Jörg; Succo, Manuel; Khenissi, Abdallah
Highlights: Demonstration of stable operation of a DSG power plant. DSG is functional even during highly fluctuating DNI. Mass flow is divided equally into parallel loops in evaporator and superheater. Big buffer capacity of steam drum and longer pipelines stabilise operation. Valuable lessons on the improvement of control strategy for DSG were learned. Abstract: TSE1 is the first solar thermal power plant operating in Southeast Asia. It was planned by Solarlite GmbH with support of Tiede- & Niemann GmbH, both German based. It is the first power plant with direct steam generation (DSG) concept and superheating in parabolic troughs. The solar field has a nominal power of 19 MWth driving a 5 MWel turbine by superheated steam at 30 bar and 330 °C. During 2010/2011 Solarlite built the solar field, while the later owner and operator Thai Solar Energy (TSE) from Bangkok built the power block, in Kanchanaburi, Thailand. TSE1 is being operated by TSE since January 2012 (Krüger et al., 2012). This publication is based on a study within the KanDis project, funded by the German Federal Ministry for Economic Affairs and Energy, in which an extensive database of records of almost 500 sensors installed in the power plant (solar field and power block) has been investigated. The data have been provided by Solarlite with a time resolution of about 1 min. Within the KanDis project, a stable operation could be demonstrated (Khenissi et al., 2015; Krüger et al., 2016). Even under the fluctuating irradiance conditions in the rainy season of Thailand, the turbine could be operated well and generate electricity. Evaluation of the operation data has helped to learn more about DSG behaviour. The TSE1 layout and the implemented control strategies were evaluated and strategies for improvement of TSE1 are suggested within this paper. From the experiences with the TSE1 power plant, conclusions could be drawn to improve the layout and control of future DSG plants.